Anthropometry and health for sport - Kagawa, Masaharu (2017)
© Springer Nature Singapore Pte Ltd. 2017. This chapter describes current applications of anthropometry for the assessment of health and nutritional status, to monitor adequate growth and to screen for and diagnose lifestyle-related diseases. A healthy body is required if sport performance is to be maximized. Anthropometric measurements need to be undertaken by trained anthropometrists with appropriate knowledge in order to provide meaningful information on health and nutritional status of individuals and the target population.